Renal Mass and Localized Renal Cancer: Evaluation, Management, and Follow-up: AUA Guideline: Part II. Issue 2 (11th August 2021) - Campbell, Steven C.; Uzzo, Robert G.; Karam, Jose A.; Chang, Sam S.; Clark, Peter E.; Souter, Lesley
Abstract : Purpose: This AUA Guideline focuses on active surveillance (AS) and follow-up after intervention for adult patients with clinically-localized renal masses suspicious for cancer, including solid enhancing tumors and Bosniak 3/4 complex cystic lesions. Materials and Methods: In January 2021, the Renal Mass and Localized Renal Cancer guideline underwent additional amendment based on a current literature-search. This literature search retrieved additional studies published between July 2016 to October 2020 using the same Key Questions and search criteria from the Renal Mass and Localized Renal Cancer guideline. When sufficient evidence existed, the body of evidence was assigned strength-rating of A (high), B (moderate), or C (low) for support of Strong, Moderate, or Conditional Recommendations. In the absence of sufficient evidence, additional information is provided as Clinical Principles and Expert Opinions (table 1 ). Results: AS with potential delayed intervention should be considered for patients with solid, enhancing renal masses <2cm or Bosniak 3-4 lesions that are predominantly-cystic. Shared decision-making about AS should consider risks of intervention/competing mortality versus the potential oncologic benefits of intervention. Recommendations for renal mass biopsy and considerations for periodic clinical/imaging-based surveillance are discussed. After intervention, risk-based surveillance protocols are defined incorporating clinical/laboratory evaluation and abdominal/chest imaging designed to detect local/systemic recurrences and possible treatment-related sequelae, such as progressive renal-insufficiency. Conclusion: AS is a potential management strategy for some patients with clinically-localized renal masses that requires careful risk-assessment, shared decision-making and periodic-reassessment. Follow-up after intervention is designed to identify local/systemic recurrences and potential treatment-related sequelae. A risk-based approach should be prioritized with selective use of laboratory/imaging resources.